Enterobacteriaceae as a Hygienic and Sanitary Performance Indicator in the Poultry Slaughter Process - SC Caldas; T Simonetti; L Kindlein (Brazilian Journal of Poultry Science)
ABSTRACT Assessing microbial indicators during slaughter is essential for managing risks and reducing foodborne pathogens. This study aimed to evaluate and categorize the hygienic-sanitary performance of a poultry slaughter operation through the Enterobacteriaceae count (EC) in chilled carcasses, collected every hour of production, totaling 360 samples. Process variables such as slaughter speed, carcass weight, fasting time, percentage of condemnation due to contamination, and Salmonella spp. positive batches were considered. Statistics were based on descriptive data analysis and the Generalized Estimating Equations model. There was a significant difference between the medians of the first and second production shifts (1.32 versus 2.16 log10 CFU/g); p<0.001). Process variables did not correlate with the EC; however, carcass samples from positive batches for Salmonella spp. showed a significantly higher median EC result than samples from negative batches (2.79 versus 1.61 log10 CFU/g; p<0.001). The mapping of microbiological indicators, such as Enterobacteriaceae, provides a photograph of the hygienic-sanitary conditions of the slaughterhouse. This offers the opportunity to maintain hygienic self-control of the process and ensure the quality of the products.